(untitled) (Proceedings of International Educators Conference, 2024)
This article examines the theoretical basis of the emergence of tax liability and suggests ways to improve its reduction. The concept of tax liability is defined and its importance in ensuring compliance with tax legislation is highlighted. Factors that lead to the emergence of tax obligations, including the complexity of tax legislation and regulations, insufficient education and awareness of taxpayers, and the inefficiency of tax administration are discussed. In addition, the legal consequences of tax liability arising and non-payment are discussed, including fines, penalties and possible criminal charges. The document concluded that a comprehensive approach to simplifying tax legislation, increasing tax payers’ knowledge and strengthening tax administration is important in ensuring the simplification of tax legislation.